Error Performance Of Super-Orthogonal Space-Time Trellis Codes With Transmit Antenna Selection - Özdemir, Özgür; Altunbaş, İbrahim; Bayrak, Mehmet (Zenodo, 2006)
Publication in the conference proceedings of EUSIPCO, Florence, Italy, 2006